Effect of Staircase Incorporation on Seismic Performance of 6-Story RC Buildings: A Nonlinear Pushover Analysis - Samsul Abdul Rahman Sidik Hasibuan; Hakas Prayuda; Masdiana; Baskoro Abdi Praja; Annisa Adika Qolby; Muhammad Rizal; Syarbaini Lubis (Universitas Medan Area, 2026)
The seismic design of multi-story buildings requires accurate modeling and analysis to ensure structural safety during earthquakes. However, the staircase is often overlooked in traditional structural analyses. Therefore, this study aimed to examine the impact of the staircase on the seismic behavior of a six-story reinforced concrete building using nonlinear pushover analysis. The ETABS Nonlinear v.9.7.4 was used to model and analyze two variants, including one with a staircase and one without a staircase. Both models undergo nonlinear static pushover analysis with lateral loads of 1000 kN applied at each floor in the X and Y directions. Key seismic performance parameters were compared including natural periods, pushover curves, story displacements, drifts, drift ratios, and shears. The results showed that incorporating staircases significantly influences seismic response. The model with the staircase has a shorter natural period (0.71s vs. 0.82s for the first mode), showing increased stiffness. Subsequently, it also shows a higher base shear capacity (5200 kN vs. 4900 kN in the X-direction), suggesting enhanced lateral load resistance. The staircase model experiences reduced story displacements and lower drift ratios, with the maximum drift ratio decreasing from 1.03% to 0.86%. These results highlight the crucial role of staircases in improving seismic performance by increasing stiffness, enhancing lateral load capacity, and controlling displacement. In line with these findings, there is a need to incorporate the staircase in structural modeling to achieve more accurate seismic performance predictions, contributing to safer and more resilient building designs in earthquake-prone regions.